2015
DOI: 10.1080/21645515.2015.1073426
|View full text |Cite
|
Sign up to set email alerts
|

Parent HPV vaccine perspectives and the likelihood of HPV vaccination of adolescent males

Abstract: In 2013, approximately one-third of US adolescent males age 13-17 y had received ≥1 doses of HPV vaccines and only 14% had received ≥3 doses. This study used a nationally representative, online survey to explore experiences and attitudes related to HPV vaccination among parents with adolescent sons. Analyses compared the perspective of parents who do not intend to initiate HPV vaccine for ≥1 adolescent son to that of parents who are likely to initiate or continue HPV vaccination. Of 809 parents of sons age 11-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 8 publications
3
19
0
Order By: Relevance
“…4 One small study found that most parents who discussed HPV vaccination with a provider reported receiving adequate information on prevention topics. 84 In contrast, qualitative studies with parents from racial/ethnic minority backgrounds suggested some degree of dissatisfaction with HPV vaccine communication, with some parents reporting too little information, limited opportunities to ask questions, or ambiguous recommendations. 61,71,77,78,98,99 For these parents, the perception that providers were withholding information was a source of confusion that introduced doubt about the value of HPV vaccination, discouraged vaccine acceptance, and in some cases undercut parents' trust in providers.…”
Section: Satisfactionmentioning
confidence: 96%
See 2 more Smart Citations
“…4 One small study found that most parents who discussed HPV vaccination with a provider reported receiving adequate information on prevention topics. 84 In contrast, qualitative studies with parents from racial/ethnic minority backgrounds suggested some degree of dissatisfaction with HPV vaccine communication, with some parents reporting too little information, limited opportunities to ask questions, or ambiguous recommendations. 61,71,77,78,98,99 For these parents, the perception that providers were withholding information was a source of confusion that introduced doubt about the value of HPV vaccination, discouraged vaccine acceptance, and in some cases undercut parents' trust in providers.…”
Section: Satisfactionmentioning
confidence: 96%
“…However, the existing literature consistently supported the assertion that providers often communicated about HPV vaccine differently from other vaccines in discrete ways. Quantitative and qualitative studies found that providers spent longer talking about HPV vaccine than other vaccines, 11,27,35,74,76,84 endorsed HPV vaccine less strongly than Tdap and meningococcal vaccines, 11,12,22,74,87 and often presented HPV vaccine as an "optional" vaccine vs. one that was "routine" or "required." 12,22,38,74,79,91 Finally, one study found that, among providers with a preferred order for discussing adolescent vaccines, over two-third preferred to discuss HPV vaccine last.…”
Section: Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge, beliefs, and attitudes in regard to HPV, the vaccine, and the negative implications associated with the disease were present in qualitative studies in the literature. Parental refusal and gender, more specifically refusal in male adolescents, were the most common topics in regards to knowledge, beliefs, and attitudes about the HPV vaccination [17][18][19][20].…”
Section: Findings and Themes Knowledge Beliefs And Attitudesmentioning
confidence: 99%
“…Provider recommendation is critical to vaccine uptake [4-6]. Some studies suggest that adequate, clear, and accessible information for parents may enhance acceptance of a provider’s recommendation and improve confidence and trust in the system [7-9]. However, little is known about physicians’ current use of or preferences for educational materials regarding HPV vaccination.…”
Section: Introductionmentioning
confidence: 99%